Project-based pedagogy as a tool for the development of educational practices - Ochoa Londoño, Efraín Darío; Herrera Pérez, Jhan Carlos; Tello-Zuluaga, Jefferson; Ochoa Londoño, Efraín Darío; Herrera Pérez, Jhan Carlos; Tello-Zuluaga, Jefferson; Ochoa Londoño, Efraín Darío; Herrera Pérez, Jhan Carlos; Tello-Zuluaga, Jefferson (Corporación Universitaria Americana, 2022)
Introduction: The present research was approached to get the Pedagogy application for academic Projects (PPP) as a source to promote the development of educational practices witness' judgment that key informants offer in their own experience inside the educational ecosystem. Objective: To generate theoretical constructs about the Pedagogy application for academic Projects as a source to promote the educational practices development. This process is boarded up on research by a subjectivist grasp.Also, it contains the theoretical use at the time it is based on key informants' experiences, which are made up of four school teachers and two school directive executives from two Public Educational Institutions in Medellín city. Methodology: The information gathering technique that was used was the interview in-depth. The instruments' validity was carried out through a professional review by experts. Conclusion: From that perspective, it produced a knowledge less encouraging for the Formation Processes Status based on educational practices that do not get into familiar results with PPP, and this also gets separated from what is convenient since the Teachers' practice stages and the holistic development from academic needs that, in reality, presents the human context. In that way, the theorizing was emphasized in authorizing true positiveaspects and the real ones taken from PPPs, the same element that could help for the accomplishment of the educational goal, which is translated in the learners' realization under the complexity observation, the constructivism, and the rest of active pedagogical referring in modern times.